2021
DOI: 10.1016/j.jbc.2021.100499
|View full text |Cite
|
Sign up to set email alerts
|

Structural details of amyloid β oligomers in complex with human prion protein as revealed by solid-state MAS NMR spectroscopy

Abstract: Human PrP (huPrP) is a high-affinity receptor for oligomeric amyloid β (Aβ) protein aggregates. Binding of Aβ oligomers to membrane-anchored huPrP has been suggested to trigger neurotoxic cell signaling in Alzheimer’s disease, while an N-terminal soluble fragment of huPrP can sequester Aβ oligomers and reduce their toxicity. Synthetic oligomeric Aβ species are known to be heterogeneous, dynamic, and transient, rendering their structural investigation particularly challenging. Here, using huPrP to preserve Aβ o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 102 publications
(276 reference statements)
1
21
0
Order By: Relevance
“…Thus, both domains of PrP may contribute structurally to interaction with the end of the Aβ fibril. This suggestion is consistent with a recent solid-state NMR study, which demonstrated structural changes in both domains of PrP upon Aβ oligomer binding 59 .…”
Section: Discussionsupporting
confidence: 93%
“…Thus, both domains of PrP may contribute structurally to interaction with the end of the Aβ fibril. This suggestion is consistent with a recent solid-state NMR study, which demonstrated structural changes in both domains of PrP upon Aβ oligomer binding 59 .…”
Section: Discussionsupporting
confidence: 93%
“…The "amyloid-β oligomer hypothesis" , which is still under debate, states that the main reasons behind AD is the formation of soluble oligomers of Aβ [7][8][9][10] considered to be more toxic than plaques and causing selective nerve cell death [10][11][12] . Indeed, soluble Aβ oligomers (AβO) are believed to be more toxic 13 than fibrils, which precipitate as plaques, because they are able to spread across neuronal tissue and they are supposed to mediate neurotoxicity and synaptic loss through binding to membrane receptors, including the prion protein 14,15 . To assess its validity and to develop new drug candidates against AD targeting the soluble oligomers, new analytical methodologies able to finely monitor, quantify and characterize these oligomeric species are required.…”
Section: Introductionmentioning
confidence: 99%
“…While it was not shown experimentally, the images of the globular structures are indicative of biomolecular condensates formed by PrP145X via LLPS [101]. Another intriguing observation is that binding of neurotoxic Aβ oligomers to the polybasic motifs converts liquid-like droplets of full length PrP into hydrogel and induces a conformation change of PrP [97,102], suggesting that aberrant phase transition of PrP C may be associated with the activity of the PrP/Aβ complex to induce neurotoxic signaling [97]. Thus far, a possible role of LLPS in the neuroprotective activities of full length PrP or the liberated N-terminal fragments has only been indirectly demonstrated: PrP variants that lack a stress protective activity in cell culture and animal models [58,67] failed to undergo LLPS in vitro [94,99].…”
Section: The N-terminal Domain Is Necessary and Sufficient For Liquid-liquid Phase Separation Of Prpmentioning
confidence: 91%